Quantification of Coastal Change and Preliminary Sediment Budget Calculation Using SfM Photogrammetry and Archival Aerial Imagery - Rafael C. Carvalho; Ruth Reef (Geosciences, 2022)
A preliminary sediment budget for the sandy shores flanking the entrance to Western Port, a large bay in Australia, was formulated using a comparison between two Digital Surface Models (DSMs) with a 30-year interval and auxiliary shoreline data. The 1977 DSM was generated from ten aerial photographs using Structure-from-Motion (SfM) photogrammetry. Assessment of its accuracy obtained an RMSE of 0.48 m with most of the independent points overpredicting or underpredicting elevations by less than 0.5 m following manual point cloud cleaning. This technique created a 7.5 km2 surface with a Ground Sampling Distance of 34.3 cm between two coastal towns separated by a narrow channel. Comparison of the 1977 DSM to a second, light detection and ranging (LiDAR)-derived DSM from 2007 showed that a volume of ~200,000 m3 of sediment (above Mean Sea Level) was deposited at Newhaven Beach on Phillip Island, while, during the same period, ~40,000 m3 of sediment was lost from the mainland beaches of San Remo, on the eastern side of the channel. Shoreline positions extracted from aerial photographs taken in 1960 and a nautical chart published one century earlier indicate that the progradation experienced at Newhaven Beach has been possible due to provision of sediment via destabilisation of the vegetation covering the updrift Woolamai isthmus on the southeast coast of Phillip Island, whereas the retreat observed at San Remo Beach since 1960 can be attributed to the natural dynamics of the entrance, which appears to favour flood-dominance on the western side and ebb-dominance on the eastern side. While a more comprehensive balance of volumes entering and exiting the area would specifically benefit from volumetric assessments of the subaqueous part of the entrance, the general usefulness of quantifying coastal change using SfM and historical photographs is demonstrated.